Essential Medical Genetics - Connor, James Michael Ferguson-Smith, M. A. (Blackwell Scientific Publications, 1987)
An extensively revised edition of a text providing a comprehensive account of the basic principles and clinical applications of modern medical genetics. Advances in molecular genetics and the diagnostic applications of recombinant DNA technology are covered.